Chromosomal assembly of the nuclear genome of the endosymbiont-bearing trypanosomatid Angomonas deanei. Issue 1 (27th November 2020) - Davey, John W; Catta-Preta, Carolina M C; James, Sally; Forrester, Sarah; Motta, Maria Cristina M; Ashton, Peter D; Mottram, Jeremy C
Abstract: Angomonas deanei is an endosymbiont-bearing trypanosomatid with several highly fragmented genome assemblies and unknown chromosome number. We present an assembly of the A. deanei nuclear genome based on Oxford Nanopore sequence that resolves into 29 complete or close-to-complete chromosomes. The assembly has several previously unknown special features; it has a supernumerary chromosome, a chromosome with a 340-kb inversion, and there is a translocation between two chromosomes. We also present an updated annotation of the chromosomal genome with 10, 365 protein-coding genes, 59 transfer RNAs, 26 ribosomal RNAs, and 62 noncoding RNAs.